Konflik Batin dan Resolusi Religius: Studi pada Mahasiswa yang Mengalami Krisis Iman - Almira Wardah Zaen; Novila Alfiani; Ratu Heba Briliana; Yuminah Yuminah (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
Faith crisis is one of the psychological and spiritual challenges faced by university students during their identity-seeking phase. The inner conflicts that arise are often related to academic pressure, social interactions, and deep questions about belief. This study aims to explore the dynamics of inner conflict experienced by students and the role of religious resolution in their recovery process. Using a qualitative approach through in-depth interviews with five students from different religious backgrounds, the study found that faith crises can trigger psychological stress, but this can be mitigated through mature religious understanding, support from spiritual communities, and engagement in religious activities. The study highlights the importance of religious support in managing inner conflicts during the transition to early adulthood.